Fusarium verticillioides of maize plant: Potentials of propitious phytomicrobiome as biocontrol agents - Omotayo, Oluwadara Pelumi; Babalola, Olubukola Oluranti (Frontiers in Fungal Biology, 2023)
Disease outbreaks have been recorded due to exposure to Fusarium verticillioides and fumonisin, a mycotoxin produced by this fungus. F. verticillioides is a fungal pathogen of maize that causes infections, such as wilting and rotting, while contact with its fumonisin derivative manifests in the form of mild to severe illnesses in humans and animals. Maize infection by F. verticillioides causes loss or reduction in expected crop yield, thereby influencing households and nations’ economies. While several efforts have been made to control the pathogenic fungus and its occurrence in the environment, it remains a challenge in agriculture, particularly in maize production. Several microorganisms which are plant-associated, especially those associated with the rhizosphere niche have been noted to possess antagonistic effects against F. verticillioides. They can inhibit the pathogen and tackle its debilitating effects on plants. Hence this study reviews the use of rhizosphere-associated biocontrol agents, such as Bacillus spp., Pseudomonas, Enterobacter, and Microbacterium oleivorans which forms part of the phytomicrobiome in other to prevent and control this toxicogenic fungus. These microorganisms were found to not only be effective in controlling its occurrence on maize plants but are environmentally safe and promote crop yield. Keywords: Biocontrol agents; Environment; Fusarium verticillioides; Maize pathogen; Maize rhizosphere; Phytomicrobiome